High School conflicts its approach by the administration and teaching staff - Chacón Soto, Lisbeth (2011)
This paper presents a study on "Administrative approach to teaching and student conflict in the field of secondary education". Data on current global situation and national conflicts in the social and educational is presented first.The research is based on bibliographic documents which provide a comprehensive view about the challenge of those who administer education, with emphasis in conflictsthat students experience when trying to fulfill the expectations and purposes of education in Costa Rica. It also contains the results drawn from this study and suggests strategies for a preventive approach.